Critical Review of the Metallurgical Operation of the Greek Nickel Industry and Perspectives, based on the recent Industrial Experience on Smelting Reduction Process - Zografidis, Charalabos; Betsis, Konstantinos; Xenidis, Anthimos (Technical Annals, 2024)
The mining and industrial production of Greek ferronickel industry LARCO have ceased since 30.07.2022. The last LME nickel price crisis, exclusion from bank loaning, extremely high cost of electrical energy, management issues, resulted inter alia, in a prohibitive operational cost. Nevertheless, LARCO faces the challenge of restructuring and reoperation in the future, given that privatization is in progress, including the acquisition of the company’s assets to a joint venture enterprise. Within this framework, the current paper aims to contribute to the discussion for developing a new management strategy for the optimization of pyrometallurgical process, focusing on the critical step of smelting reduction. Based on industrial experience concerning open bath submerged arc electric furnaces, factors which critically affect the safety and cost-effectiveness of smelting reduction are detected and presented by means of case studies, being mainly classified as following: i) Optimal raw materials’ feed management, including laterite ores (domestic or not), solid fuels and electrode paste. Moreover, taking for granted the need for Ni-rich ‘foreign’ ores to increase the recovery and reduce the cost of the process, the extent of dependence on Fe-rich domestic ores is investigated, in order a safe and stable operation to be ensured. ii) Focus on preventive maintenance management. Substantial increase of the facilities’ operational index and cost saving is obtained, as proved by operational case studies. iii) Modern human resources management strategy. Their economical footprint is further discussed.